The Use of Songs to Improve Listening Skills in Twelfth-Grade Students of Senior High School Number 8 Jambi - Yurni, Yurni; Munawwaroh, Khidayatul; Guk-Guk, Elsa Oriana Raja (Universitas Batanghari Jambi, 2024)
This study investigates the effectiveness of using English songs as a teaching technique to improve listening skills among twelfth-grade students at SMA Negeri 8 Kota Jambi, Indonesia. Employing a true experimental design, the research compared an experimental group receiving instruction through songs with a control group receiving conventional instruction. The sample consisted of 73 students, divided into two classes. Data was collected through pre-tests and post-tests, using a listening test that involved completing song lyrics with omitted words. The study utilized quantitative analysis methods, including normality tests and t-tests, to evaluate the impact of the song-based instruction. Results indicate the use of English songs significantly enhanced students' listening skills compared to conventional methods. This research contributes to the growing body of literature on innovative approaches to English language teaching, particularly in improving listening skills in EFL contexts. The findings offer valuable insights for educators seeking to incorporate engaging and culturally rich tools in language instruction, potentially improving overall language proficiency among students.